Burn Trauma Acutely Increases the Respiratory Capacity and Function of Liver Mitochondria. Issue 4 (April 2018) - Bohanon, Fredrick J.; Nunez Lopez, Omar; Herndon, David N.; Wang, Xiaofu; Bhattarai, Nisha; Ayadi, Amina E.; Prasai, Anesh; Jay, Jayson W.; Rojas-Khalil, Yesenia; Toliver-Kinsky, Tracy E.; Finnerty, Celeste C.; Radhakrishnan, Ravi S.; et al.
ABSTRACT: Background: A complete understanding of the role of the liver in burn-induced hypermetabolism is lacking. We investigated the acute effect of severe burn trauma on liver mitochondrial respiratory capacity and coupling control as well as the signaling events underlying these alterations. Methods: Male BALB/c mice (8–12 weeks) received full-thickness scald burns on ∼30% of the body surface. Liver tissue was harvested 24 h postinjury. Mitochondrial respiration was determined by high-resolution respirometry. Citrate synthase activity was determined as a proxy of mitochondrial density. Male Sprague-Dawley rats received full-thickness scald burns to ∼60% of the body surface. Serum was collected 24 h postinjury. HepG2 cells were cultured with serum-enriched media from either sham- or burn-treated rats. Protein levels were analyzed via western blot. Results: Mass-specific ( P  = 0.01) and mitochondrial-specific ( P  = 0.01) respiration coupled to ATP production significantly increased in the liver after burn. The respiratory control ratio for ADP ( P  = 0.04) and the mitochondrial flux control ratio ( P  = 0.03) were elevated in the liver of burned animals. Complex III and Complex IV protein abundance in the liver increased after burn by 17% and 14%, respectively. Exposure of HepG2 cells to serum from burned rats increased the pAMPKα:AMPKα ratio ( P  < 0.001) and levels of SIRT1 ( P  = 0.01), Nrf2 ( P  < 0.001), and PGC1α ( P  = 0.02). Conclusions: Severe burn trauma augments respiratory capacity and function of liver mitochondria, adaptations that augment ATP production. This response may be mediated by systemic factors that activate signaling proteins responsible for regulating cellular energy metabolism and mitochondrial biogenesis.